الدور التكاملي لمؤسسات المجتمع في استنقاذ المدمن - عبدالرحمن، سناء عبدالحميد علي (جامعة الأزهر - كلية البنات الإسلامية بأسيوط, 2020)
تعد ظاهرة الإدمان مأساة إنسانية لما تسببه من آثار مدمرة للمجتمعات في شتى المجالات (نفسية واجتماعية واقتصادية)، أما من حيث الآثار النفسية فإن فيها ذهاب العقل الذي ميز الله به الإنسان على غيره من المخلوقات والصحة والعافية، فالإدمان أشبه بخلايا السرطان التي تنزل بالبدن فترعاها ولا تتركه إلا مهمشا محطما، كذلك وبحسب تقرير منظمة الصحة العالمية تبين أنه يلقي حتفه كل سنة ما يقرب من 250000 (مائتين وخمسون ألف) شخص جراء تناول جرعات مفرطة وجراء الإصابة بأمراض مرتبطة بالمخدرات، ويتسبب الكحول في وفاة ما يقرب من (2.3) مليون نسمة، ويتسبب التبغ في وفاة (5.1) ملايين نسمة، وأما من حيث الآثار الاجتماعية فمنها ما يتسبب عن الإدمان من هدم كيان الأسر وعدم تماسك المجتمع، وانتشار سلوكيات دخيلة على المجتمعات العربية والإسلامية والتي تعد مخالفة للعادات والأعراف والمثل والقيم الدينية، وأما الآثار الاقتصادية فتتمثل في ضياع الثروات عن طريق الإنفاق على المخدرات ذاتها من ناحية ومن ناحية أخرى ما يسببه من قلة إنتاج الدول نتيجة تشرد الأحداث وجرائمهم وانتشار الدعارة.
The phenomenon of addiction is a human tragedy because of its devastating effects on societies in various spheres (psychological, social and economic). As for the psychological effects, the mind that God distinguished human beings from other creatures, health and wellness, addiction is like cancer cells that come down to the body and leave it only marginalized, as well as according to the report of the World Health Organization shows that he dies nearly every year, 250.000 (two hundred and fifty thousand) people for overdoses and drug-related diseases, Alcohol causes the death of nearly 2.3 million people, and tobacco causes the death of (5.1) million people, but in terms of social effects, including the addiction caused by the destruction of the entity of families and the incoherence of society, and the spread of behaviors alien to Arab and Muslim societies, which is contrary to customs The economic implications are the loss of wealth through the expenditure of drugs themselves, on the one hand, and on the other hand, caused by the lack of state production as a result of the displacement of juveniles, their crimes and the spread of prostitution.
Keywords: الإدمان -- المخدرات -- المدمن -- مؤسسات المجتمع -- الفقه الإسلامى